2002
DOI: 10.1023/a:1020102604090
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The oxidation kinetics of high-purity nickel were studied between 500 and 1200°C, in pure oxygen at atmospheric pressure, for aûerage oxide-scale thicknesses of 1, 5, 10, and 30 µm. In the oûerall temperature range studied, a decrease in the parabolic rate constant k p with increasing scale thickness was obserûed. Depending on temperature and oxide-scale thickness, growth kinetics can be interpreted as a mixture of parabolic-and cubic-growth kinetics. Possible correlations between growth kinetics and microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 44 publications
10
39
0
1
Order By: Relevance
“…The dependence of oxidation rate on crystallographic orientation has also been suggested for Fe and Cr [9][10][11][12][13][14]. In oxidation studies on Ni single crystals, more rapid oxidation is consistently observed on (001) faces than on (111) faces [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The dependence of oxidation rate on crystallographic orientation has also been suggested for Fe and Cr [9][10][11][12][13][14]. In oxidation studies on Ni single crystals, more rapid oxidation is consistently observed on (001) faces than on (111) faces [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 83%
“…In contrast, single crystal studies show that differences in the rate of oxidation for different surface orientations persist up to at least 24 hours of oxidation [10,12,16,27]. Two different approaches are used to quantify the diminishing effects of substrate orientation on oxidation rate in Ni.…”
Section: Orientation Dependent Oxidation In Fcc Metalsmentioning
confidence: 99%
“…10) There have been many investigations on the high temperature oxidation of nickel and the kinetics followed the parabolic rate law, which is mainly determined by the diffusion of nickel ion. 7,[10][11][12][13][14][15] The purpose of this study is to demonstrate quantitative estimation of void formation in NiO scale, and to compare microstructures of the oxide scales formed on nickel at 1373 K with the estimation. Figure 1 shows a schematic illustration of chemical potential distributions of nickel and oxygen in NiO scale.…”
Section: Introductionmentioning
confidence: 99%
“…Les données trouvées dans la littérature (2-12) relatives aux cinétiques de croissance de NiO peuvent être regroupées dans un même domaine (zone grisée de la figure 1) dans un diagramme d'Arrhenius repré-sentant l'évolution de la constante parabolique d'oxydation k p en fonction de l'inverse de la température. Pour les températures supérieures à 1 000°C, les valeurs des constantes k p sont en bon accord les unes avec les autres (13). La comparaison des données des coefficients de diffusion du nickel et de l'oxygène dans NiO (2, 14-29) avec les valeurs des constantes k p ( fig.…”
Section: ■ Introductionunclassified